PENGARUH KEPEMILIKAN BPJS KESEHATAN TERHADAP PEMANFAATAN PELAYANAN KESEHATAN DI UPT PUSKESMAS MANCAK TAHUN 2023 - Rosida, Ida; Umalah, Umalah (LPPM Institut Pendidikan Nusantara Global, 2023)
The new paradigm of health services in Indonesia is currently focused on health services that are disease prevention and health promotion by paying attention to quality and health financing guarantees. The formulation of the problem in this study is the Effect of Health BPJS Ownership on Utilization of Health Services at UPT Puskesmas Mancak. The general aim of this research is to know the influence of BPJS Health Ownership on the Utilization of Health Services at UPT Puskesmas Mancak. Benefits of Research As input material for health service agencies about the importance of the Effect of BPJS Health Ownership on Health Service Utilization at UPT Puskesmas Mancak. Adding BPJS Card Ownership to officers regarding the Effect of BPJS Health Ownership on the Utilization of Health Services at UPT Puskesmas Mancak.